IMPROVING EDIBLE FILM QUALITY USING MODIFIED WATER YAM (Dioscorea alata L) STARCH - Ulyarti; Indriyani; Rahayu Suseno; Siti Nursela; Hesti Megawati; Irma Rahmayani; Nazarudin (Jurnal Teknologi Pertanian, 2022)
The existed edible films made of water yam starch tend to have a low quality which is indicated by high WVTR value and low mechanical strength. Addition of modified starch can decrease the WVTR value and improve the mechanical properties. The purpose of this study is to obtain the ratio of starch paste volume to ethanol volume which produces modified water yam starch and to improve the quality of the edible film by adding modified water yam starch. This research was conducted in 2 stages, which are the modification of water yam starch using the precipitation method and the making of edible films using several levels of modified water yam starch concentration. The first stage of the study was designed to produce modified starch using the treatment of the ratio of starch paste volume to ethanol volume. There are 5 treatment ratios used, which were 1:5, 1:7.5, 1:10, 1:12.5, and 1:15. The results showed that the different ratios of starch paste volume to ethanol volume resulted in different sizes of modified starches. The ethanol volume ratio of 1:5 resulted in a granular starch with the most damage in its morphology, and the smallest particle size detected was 1.135x1.767 µ, with the yield of modified starch was 80.5%. The addition of modified water yam starch of as much as 20%, which was modified using a ratio of paste volume to ethanol volume of 1:5, succeeded in improving the quality of the edible film of water yam starch by reducing the value of the water vapor transmission rate and increasing the compressive compressive strength.